The practicality and effectiveness of supplementary bright light for reducing jet-lag in elite female athletes - Thompson, A.; Batterham, A. M.; Jones, H.; Gregson, W.; Scott, D.; Atkinson, G. (International Journal of Sports Medicine, 2013)
Although bright light can alter circadian timing, the practicality and effectiveness of supplementary bright light for reducing jet-lag symptoms in world-class athletes is unclear. Therefore, we randomised 22 world class female footballers to a bright light intervention or control group before a flight from USA to Europe. Intra-aural temperature, grip strength, sleep and various jet-lag symptoms were measured serially. For 4 days, the intervention participants were exposed, in pairs within their rooms, to 2 500 lux of bright light at appr. 50 cm for 45-60 min at a time-of-day predicted to accelerate circadian adjustment. On post-flight day 1, indoor light transiently increased intra-aural temperature by 0.38°C (95%CI: 0.16 to 0.60, P=0.001) and increased overall jet-lag rating by appr. 1 unit. Light had negligible effects on functioning, diet, bowel and sleep symptoms, which varied substantially between- and within-subjects. In conclusion, supplementary indoor light administered within the schedule of world-class athletes was not substantially effective for reducing jet-lag symptoms after a flight from the USA-Europe. Ours is the first study of the practical effectiveness of supplementary bright light in world class athletes, although sample size was naturally small, compromises were required to implement the intervention and there appears to be large inter-individual variation in the perception of what constitutes jet-lag.